Diversity of plants used in traditional veterinary medicine in Central-Eastern Burkina Faso: Plants used in Traditional Veterinary Medicine - Zerbo, Issouf; Balima, Larba Hubert; Sanou, Charles Lamoussa; Thiombiano , Adjima (Ethnobotany Research and Applications, 2025)
Background: In the West African Sahel, ethnoveterinary medicine is widely practiced by livestock farmers but remains poorly documented. This study aims to describe the medicinal plants and traditional recipes used for treating major animal diseases in Burkina Faso, specifically in the Centre-Eastern region. Methods: Semi-structured surveys were conducted from August to October 2024 with 120 livestock farmers randomly selected from five communes in the Centre-Eastern region of Burkina Faso. Data were analyzed using relative frequency of citations and Sankey diagrams. Results: A total of 38 animal diseases were reported, with diarrhea (11%), trypanosomiasis (10%) and retained placenta (9%) being the most frequently cited. The primary causes of animal diseases were nutritional (28.72%), parasitic (26.28%) and environmental (16.26%). Livestock farmers used 88 plant species from 73 genera and 34 families to treat these diseases. The most represented families were Fabaceae (21.59%), Malvaceae (9.08%) and Poaceae (6.82%). The most frequently used species were Khaya senegalensis (34.02%), Parkia biglobosa (18.40%), Terminalia leiocarpa (10.00%), Vachellia nilotica (9.03%) and Vitellaria paradoxa (8.00%). All plant parts were used in the disease treatment, with bark (35.56%), leaves (21.08%) and fruits (11.88%) being the most frequently used. Six preparation methods were identified in the formulation of ethnoveterinary remedies, with maceration (38.82%) and decoction (34.04%) being the most common. Approximately 86.45% of the recipes were plant-based, while 13.55% included mineral products. Eight administration routes were reported with oral (46.15%), anal (17.31%) and topical (17.31%) applications being the most frequent. Conclusions: This study documents the use of plants in traditional veterinary medicine practiced by livestock farmers and provides important information to complement modern veterinary medicine in addressing livestock health issues. Keywords: Ethnoveterinary medicine, Animal diseases, Medicinal plants, Sahel.